PENGAWASAN DAN AKUNTABILITAS APARATUR DALAM PERSPEKTIF ETIKA BIROKRASI: STUDI KASUS PADA PEMERINTAH DAERAH KABUPATEN CIANJUR - Iwan Satibi (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This article aims to find out the problems of supervision and accountability, as well as the strategy of the Cianjur Regency Government in carrying out supervision and accountability in ethical perspectives. This research was conducted using descriptive methods with a qualitative approach. The ethical perspective on supervision and public accountability within the Cianjur Regency Government is actually an "oasis" in the midst of weakening public confidence in the government apparatus. Through effective supervision, the Cianjur Regency Government will be able to anticipate and overcome various deviations that have so far remained a concern of the community. Whereas through good and right public accountability a professional, transparent, accountable, credible and corruption-free, collusion and nepotism administration can be obtained.